Zeitgeschichte : "blow-up". - Honnef, Klaus; Osterwold, Tilman; Haus am Waldsee, Berlin; Kunstverein Hamburg; Frankfurter Kunstverein, Frankfurt; Kunstmuseum Luzern, Luzern; Rheinisches Landesmuseum, Bonn (Stuttgart : Württembergischer Kunstverein, 1987)
Kosuth, Joseph ; Hilliard, John ; Abramovic, Ulay & Marina ; Sherman, Cindy ; Evergon ; Van Zak, Hatty ; Clegg & Guttmann ; Wall, Jeff ; Wallace, Ian ; Burkhard, Balthasar ; Kummer, Raimund ; Webb, Boyd ; Boltanski, Christian ; Rousse, Georges ; Förg, Günther ; Klein, Astrid ; Sieverding, Katharina ; Bonvie, Rudolf ; Baldessari, John ; Kruger, Barbara
Zeitgeschichte "blow-up", Württembergischer Kunstverein, Stuttgart ; Haus am Waldsee, Berlin ; Kunstverein Hamburg ; Frankfurter Kunstverein, Frankfurt ; Kunstmuseum Luzern ; Rheinisches Landesmuseum, Bonn
kunstcatalogus